Creating Academic-Museal Dialogue In-Between Ivory Towers and Unwritten Pages: Tsinghua University Art Museum and Its Collection of Chinese Contemporary Calligraphy - Hertel, Shao-Lan (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2020)
Addressing the pedagogical framework of university art museums and the potentials and challenges they carry as innovative academic-museal models, this article explores recursive spheres of educational institutions shaping the theory, practice, and reception of art in present-day Mainland China. Through a critical discussion of TAM’s Chinese contemporary calligraphy collection, time-and-space-specific functions and meanings constituting zones of cultural dialogue and negotiation between different generations of Tsinghua scholars are carved out. Shaped by and deeper shaping cultural-national identity in the Chinese collective (sub-) consciousness, 2019, China’s “Big Year for Anniversaries”, affords the crucial moment to reflect upon her modern history, omnipresent and omniabsent alike.